Modern principles of public administration of pharmaceutical supply for the population in emergency situations - P. V. Olіynуk; B. P. Hromovyk (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
In conditions of the emergency situations’ amount increasing the readiness of the state to provide affected people and all other segments of the population with full pharmaceutical provision is important.